Work-Family Conflict Disaster: From Organizational Commitment to Job Satisfaction - Purwanto, Agus; Hidayat, Dylmoon; Asbari, Masduki (International Journal of Social and Management Studies, 2021)
- This study aimed to measure the effect of work-family conflict on job satisfaction through organizational commitment (affective, continuence, normative) as mediation. The data collection was done by simple random sampling to 251 population of woman employee in an automotive industry in Tangerang. The returned and valid questionnaire results were 170 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict have not significant effect on job satisfaction, work-family conflict have significant effect on organizational commitment (affective, continuence, normative), and organizational commitment (continuence and normative) have mediating effect on relationship between work-family conflict and job satisfaction, except affective commitment have not significant effect on job satisfaction. This new research proposed a model for building job satisfaction among women employee of automotive industry in Tangerang through enhancing organizational commitment and by manage the work-family conflict. This research could pave the way to improve woman employee readiness in facing the era of industrial revolution 4.0.